2019
DOI: 10.1155/2019/7196528
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of 3D Printing Assistance in the Spinal Deformity Surgery

Abstract: Background The pedicle screw is one of the main tools used in spinal deformity correction surgery. Robotic and navigated surgeries are usually used, and they provide superior accuracy in pedicle screw placement than free-hand and fluoroscopy-guided techniques. However, their high cost and space limitation are problematic. We provide a new solution using 3D printing technology to facilitate spinal deformity surgery. Methods A workflow was developed to assist spinal deformity surgery using 3D printing technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
(38 reference statements)
1
15
0
8
Order By: Relevance
“…Planning for intraoperative use of navigation must take into account the imaging system and navigation platform available at the surgeon's facility. Use of active navigation without intraoperative CT imaging has been shown as a viable and cost-effective alternative to passive image-based 3D navigation platforms (8). Utilizing preoperative CT based drill guides, Sugawara et al reported 98.5% accuracy with screw placement in the cervicothoracic spine (9).…”
Section: Intraoperative Navigationmentioning
confidence: 99%
“…Planning for intraoperative use of navigation must take into account the imaging system and navigation platform available at the surgeon's facility. Use of active navigation without intraoperative CT imaging has been shown as a viable and cost-effective alternative to passive image-based 3D navigation platforms (8). Utilizing preoperative CT based drill guides, Sugawara et al reported 98.5% accuracy with screw placement in the cervicothoracic spine (9).…”
Section: Intraoperative Navigationmentioning
confidence: 99%
“…С другой стороны, избыточная площадь контакта требует обширной диссекции мягких тканей и затрудняет визуализацию [18]. Включение в зону контакта граней остистого отростка при определенной его конфигурации может привести к невозможности совместить шаблон с задними структурами [13]. Многие авторы в качестве опорной точки с успехом использовали верхушку остистого отростка [12,13,15,[27][28][29].…”
Section: материал и методыunclassified
“…Включение в зону контакта граней остистого отростка при определенной его конфигурации может привести к невозможности совместить шаблон с задними структурами [13]. Многие авторы в качестве опорной точки с успехом использовали верхушку остистого отростка [12,13,15,[27][28][29]. Почти все исследователи применяли одноуровневые шаблоны [12, 13, 15-18, 22-24, 26, 27, 29], так как при этом минимизируется риск неточности позиционирования за счет смещения соседних позвонков.…”
Section: материал и методыunclassified
See 2 more Smart Citations